1983
DOI: 10.1007/bf00042997
|View full text |Cite
|
Sign up to set email alerts
|

Large deformations near a tip of an interface-crack between two Neo-Hookean sheets

Abstract: This paper contains an asymptotic investigation -within the nonlinear theory of elastostatic plane stress -of the deformations and stresses near the tips of a traction-free interface-crack between two dissimilar semi-infinite Neo-Hookean sheets. The results obtained are free of oscillatory singularities of the kind predicted by the linearized theory, which would require the two deformed faces of an interface-crack to overlap in the vicinity of its tips. Instead, the crack is found to open smoothly near its end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
162
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 18 publications
4
162
0
Order By: Relevance
“…Kirchhoff stress does not vary significantly throughout the thickness, and that the planer faces are free of loads, Knowles and Sternberg (1983) showed…”
Section: Governing Equationsmentioning
confidence: 96%
“…Kirchhoff stress does not vary significantly throughout the thickness, and that the planer faces are free of loads, Knowles and Sternberg (1983) showed…”
Section: Governing Equationsmentioning
confidence: 96%
“…He observed that an antisymmetric solution is impossible and that crack opening at the crack tip still exists under mode II conditions. Also of great interest was the analysis of Knowles and Sternberg [1983], who studied the crack-tip field of an interface crack in a neo-Hookean bimaterial and found that the classical oscillatory singularities disappear. The asymptotic analysis of a crack in incompressible hyperelastic homogeneous materials and bimaterials was examined further by Geubelle and Knauss [1994a;1994b;1994c].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behaviour of the material described by (2.3) is of a hardening-type, as can be observed by imposing a three-dimensional homogeneous deformation corresponding to a uni-axial stress and evaluating the stress response in terms of Cauchy stresses (cf. [12] p. 269). The differences with respect to a classic incompressible neo-Hookean material are illustrated in [7], To maintain a state of plane stress, the components of the deformation gradient F are found to be [13,14] The last quantity denotes the principal stretch with the :r3-axis as the associated principal axis.…”
Section: Introductionmentioning
confidence: 99%
“…3These components must be considered as their restriction to the middle plane. A modern and accurate description of the fundamental relations of nonlinear plane stress theory can be found in a paper by Knowles and Sternberg [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation